2005
DOI: 10.1088/0022-3727/38/12/027
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of high-energy GARPUN KrF laser interaction with solid and thin-film targets in ambient air

Abstract: Hydrodynamic regimes of KrF laser interaction with solid and thin-film targets in air at atmospheric and reduced pressures were investigated at the high-energy GARPUN facility. These experiments were performed with 100 J, 100 ns laser pulses in planar focusing geometry and compared with numerical simulations with the ATLANT code to verify the concept of the laser-driven shock tube (LST). Strong shock waves (SWs) are produced in the LST and the gas is accelerated to hypersonic velocity due to the deposition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…Planar SW with velocities as high as 30 km/s were initiated toward the laser beam by erosion plasma blow-off in rarefied air when 100-J, 100-ns KrF laser pulses irradiated solid targets (Zvorykin et al, , 2004a(Zvorykin et al, , 2004bLebo et al, , 2004Bakaev et al, 2005;Krasnyuk & Lebo, 2006). In a forward direction, the SW was pushed by thin polystyren (CH) films accelerated by free-expanding plasma up to velocities 3.5 km/s independently of the gas density.…”
Section: Liquid-filled Laser-driven Shock Tube Conceptmentioning
confidence: 99%
See 2 more Smart Citations
“…Planar SW with velocities as high as 30 km/s were initiated toward the laser beam by erosion plasma blow-off in rarefied air when 100-J, 100-ns KrF laser pulses irradiated solid targets (Zvorykin et al, , 2004a(Zvorykin et al, , 2004bLebo et al, , 2004Bakaev et al, 2005;Krasnyuk & Lebo, 2006). In a forward direction, the SW was pushed by thin polystyren (CH) films accelerated by free-expanding plasma up to velocities 3.5 km/s independently of the gas density.…”
Section: Liquid-filled Laser-driven Shock Tube Conceptmentioning
confidence: 99%
“…By increasing a distance between resonator mirrors, an output beam was made slightly convergent. It had a reduced cross section of 10 Â 10 cm when arrived at two-component homogenizing system consisting of a prism raster 1 and a lens (Zvorykin et al, 2004a;Bakaev et al, 2005). By splitting an incident beam into 25 individual 2 Â 2-cm beamlets and overlapping them at a focal plane (raster effective focal length F eff ¼ 1000 mm) this raster provided non-uniformity less then a few percents across the square spot, which could be resized by adding a focusing lens with an appropriate focal length.…”
Section: Garpun Krf Laser Facilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The paper 'Hydrodynamics of high-energy GARPUN KrF laser interaction with solid and thin-film targets in ambient air' by Bakaev et al [1] reported the study of hydrodynamic regimes of KrF laser interaction with solid and thin-film targets in air. The experiments were performed with 100 J, 100 ns pulses from the ultra-violet excimer laser installation 'GARPUN' at the Lebedev Physical Institute (Moscow).…”
mentioning
confidence: 99%
“…Figures 24(a) and (b) in the paper [1] have to be replaced by figures 1(a) and (b) in this Addendum.…”
mentioning
confidence: 99%